Stakeholders' attitudes and beliefs towards the bilingual pedagogy of Islamic studies subject in a Malaysian international Islamic school - Tahir, Syeda Rabia; Maarof, Nooreiny (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2021)
The bilingual pedagogy of the Islamic studies subject is commonly practiced in most private and international schools worldwide. This subject is most often taught and learned in Arabic and one other language. In Islam, Arabic is the language of the normative sources, the Qur'an, and the Sunnah (prophetic tradition), and a large part of the classical tradition of Islamic education. A challenging problem for many students is limited proficiency in Arabic and the other language used to teach the subject. The common other language used is often English. Some international schools advocate the bilingual teaching of Islamic studies using Arabic and English to address this problem. This study investigates the attitudes and beliefs of the stakeholders (the school principal, Islamic studies subject teachers, students of Islamic studies subject, and their parents) towards the bilingual pedagogy of Islamic studies. A case study approach has been adopted whereby a private international Islamic school in Kuala Lumpur has been selected as the study site. The study comprises two phases: (1) A survey questionnaire distributed among the school principal, the subject teachers, students of Islamic studies, and their parents, and (2) Interviews were conducted with the school principal and teachers teaching Islamic studies subjects. The questionnaire's statistical data analysis and the content analysis of the interview protocols contributed to the study's findings. It revealed that all stakeholders had positive attitudes and beliefs towards the bilingual pedagogy of Islamic studies subject. Future research can address and support language policies and practice on bilingual education for Islamic studies subject.